2011
DOI: 10.1155/2011/458684
|View full text |Cite
|
Sign up to set email alerts
|

Does Large Genome Size Limit Speciation in Endemic Island Floras?

Abstract: Genome sizes in plants vary by several orders of magnitude, and this diversity may have evolutionary consequences. Large genomes contain mainly noncoding DNA that may impose high energy and metabolic costs for their bearers. Here we test the large genome constraint hypothesis, which assumes that plant lineages with large genomes are diversifying more slowly Knight et al. (2005), using endemic floras of the oceanic archipelagos of the Canaries, Hawaii, and Marquesas Islands. In line with this hypothesis, the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
3
11
1
Order By: Relevance
“…crassifolius. Notwithstanding, while the reduction of GS observed here is in line with the current view that larger GSs might limit speciation in island floras (Kapralov & Filatov, 2011), it remains to be demonstrated whether the increase in number of rDNA loci has been relevant for the colonisation and subsequent explosive radiation of Cheirolophus in the Canary and Madeira archipelagos. Chromosome numbers in bold are those that are new or reassessed/confirmed in this study.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…crassifolius. Notwithstanding, while the reduction of GS observed here is in line with the current view that larger GSs might limit speciation in island floras (Kapralov & Filatov, 2011), it remains to be demonstrated whether the increase in number of rDNA loci has been relevant for the colonisation and subsequent explosive radiation of Cheirolophus in the Canary and Madeira archipelagos. Chromosome numbers in bold are those that are new or reassessed/confirmed in this study.…”
Section: Discussionsupporting
confidence: 87%
“…-There is growing evidence that oceanic island colonisations tend to involve species with smaller GSs than their continen tal counterparts (e.g., Cheirolophus, Garnatje & al., 2007;Schiedea, Kapralov & al., 2009; Veronica L., Meudt & al., 2015). Indeed, this trend is seen even at the level of whole floras (e.g., in Macaronesia, Suda & al., 2003;2005; in Marquesas, Macaronesian and Hawaiian islands, Kapralov & Filatov, 2011). It has also been observed that genera of oceanic island floras that undergo species radiations have significantly smaller GSs than nonradiating genera (e.g., in Canarian flora, Pérez de Paz & CaujapéCastells, 2013).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…range from 0.73 to 3.19 pg, including some of the highest values in the genus, but with 1Cx‐values ranging from 0.24 to 0.52 pg (2.2‐fold variation), including some of the lowest. The low 1Cx‐values found in subgenus Pseudoveronica (the only insular radiation in the genus) are in line with studies showing that insular endemic radiations in the Canary, Hawaiian and Marquesas Islands have smaller genome sizes relative to the mainland flora (Suda, Kyncl & Jarolímová, ; Kapralov & Filatov, ). The extent to which the New Zealand endemic flora follows this pattern is unknown, as phylogenetic studies of genome size are lacking, and indeed very few (< 10%) native angiosperms have had their genome sizes estimated.…”
Section: Discussionsupporting
confidence: 82%
“…Although the concept of the LGCH was originally framed using interspecific genome size comparisons, intraspecific comparisons better control for phylogenetic differences among taxonomic groups. Furthermore, the LGCH has not been explicitly tested using manipulative experiments (but see Kapralov and Filatov 2011, Carta and Peruzzi 2016 for correlative studies) and has never been tested at the intraspecific level.…”
Section: Introductionmentioning
confidence: 99%